2022
DOI: 10.1186/s13722-022-00316-3
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative barriers to retention in methadone treatment among adults from rural and small urban communities

Abstract: Background Though methadone has been shown to effectively treat opioid use disorder, many barriers prevent individuals from accessing and maintaining treatment. Barriers are prevalent in less populated areas where treatment options are limited. This study examines barriers to retention in methadone treatment in a small Midwest community and identifies factors associated with greater endorsement of barriers. Methods Patients at an opioid treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Buprenorphine and naltrexone, acting as partial agonists and antagonists to MOR, respectively, have played roles in reducing opioid craving, mitigating withdrawal symptoms, and preventing relapse [6][7][8]. Despite the effectiveness of Medications for OUD (MOUDs) [9,10], challenges persist, including poor patient retention, increased overdose risks, low efficacy [6,11], and undesired side effects [12,13]. Due to lower patient compliance with current treatments, sustained-release formulations of buprenorphine and naltrexone have been developed, which addressed some of these challenges [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Buprenorphine and naltrexone, acting as partial agonists and antagonists to MOR, respectively, have played roles in reducing opioid craving, mitigating withdrawal symptoms, and preventing relapse [6][7][8]. Despite the effectiveness of Medications for OUD (MOUDs) [9,10], challenges persist, including poor patient retention, increased overdose risks, low efficacy [6,11], and undesired side effects [12,13]. Due to lower patient compliance with current treatments, sustained-release formulations of buprenorphine and naltrexone have been developed, which addressed some of these challenges [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also unknown whether Medicaid coverage of OTP services would have different impacts for those already recognized as needing treatment (e.g., enrolled with an OUD diagnosis) compared to those without. Additionally, while expanding Medicaid coverage of OTP services removed the cost barrier, prior studies have identified that distance from an OTP reduces methadone use and treatment duration, [8][9][10][11][12][13][14] and there are wide disparities in access to OTPs across the United States, particularly in nonmetropolitan areas. 10,15,16 To that end, we also examine whether these known barriers (i.e., travel distance and residing in a nonmetropolitan area) impacted methadone initiation and treatment duration following Medicaid coverage of methadone treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Unfortunately, factors associated with decreased retention in MTD are often those associated with more severe illness such as concurrent use of non-opioid substances (eg, stimulants), 15 comorbid psychiatric illness, 16 and inadequate social support. 17 Many factors can impact abstinence and retention in MTD and these 2 outcomes are closely related. 18 - 20 One intervening (mediating/moderating) variable in effective MTD is dose because under-dosing is associated with increased likelihood of continued illicit opioid use, and this ongoing opioid use often results in discharge from care.…”
Section: Introductionmentioning
confidence: 99%